A Victorian fraudster and bigamist: gentleman or criminal? - Woolnough, Guy N. (Criminology & criminal justice, 2019)
This article examines the case of a Victorian gentleman who operated at the tipping point between respectable gentleman and habitual criminal. The case of Henry Wilshin allows an exploration of ideas of class and respectability in Victorian England and the problematics of the distinction between the gentleman and the convict: an analysis of Wilshin’s escapades places the deconstruction of the ‘crimes of the law-abiding’ in a Victorian context. The issues remain relevant today in debates concerning the banking industry. In the mid-19th century the expanding commercial enterprise of industrial Britain presented opportunities that were grasped by the unscrupulous, but the distinction between licit and illicit activity was far from clear. A gentleman offender like Henry Wilshin challenged Victorian assumptions of respectability. This article analyses Wilshin’s career in the context of Victorian ideas of middle-class respectability and the operations of commerce. Neutralization theory will be advanced to reconcile the contradictions in Wilshin’s life.